Strike - MacHale, D. J. (New York, New York : Razorbill, a division of Penguin Young Readers Group, 2014)
Once again, Tucker Pierce and friends must fight for their lives against the better-equipped SYLO, and they will risk nearly everything to keep each other safe the battle's climax nears.
Keywords: War -- Fiction; Conspiracies -- Fiction; Adventure and adventurers -- Fiction; Survival -- Fiction; Science fiction; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Science & Technology; JUVENILE FICTION / Boys & Men